Tożsamość peryferyjna. Tożsamość centrystyczna. Lokalne i globalne kłopoty z tożsamością - Megier, Maja (Przegląd Politologiczny, 2018)
Can one talk about identities corresponding to the periphery-center relation, identities that are an individual aspect of a group’s position on the developmental axis, or that position in the global system of power and authority? It appears that this supposition is not without sense or foundation. A peripheral identity is related to a sense of exclusion, marginalization, being undervalued, inferiority complex, backwardness, being ‘worse’, and isolated. This can inspire various resentments, aggression, hatred, a will to win appreciation at any cost, and retaliation. It can also produce stagnation and resignation, or cause mass migration to the actual or apparent center because ‘life goes on somewhere else’ and one should not waste it in the peripheries, doomed to an existence without any prospects of positive change. A centrist identity is primarily the political version of ethnocentrism, most frequently tinted with nationalism. The feeling that we are the center of the world may have nothing in common with the geopolitical, cultural or economic reality. Since we are in the center, by definition we are better off, in any aspect that counts. A centrist identity identifies the group interest with the global interest, and it ignores the interests of the peripheries, which tend to be despised. The tendency to treat other cultures as peripheral towards our own is deeply rooted in common thinking, as well as in cultural anthropology. ‘Centrist patriotism’ can transform into chauvinism and lead to a justification for discrimination of the peripheries in many ways.